Marine Peptide-N6NH2 and Its Derivative-GUON6NH2 Have Potent Antimicrobial Activity Against Intracellular Edwardsiella tarda in vitro and in vivo - Han, Huihui; Teng, Da; Mao, Ruoyu; Hao, Ya; Yang, Na; Wang, Zhenlong; Li, Ting; Wang, Xiumin; Wang, Jianhua (Frontiers in Microbiology, 2021)
Edwardsiella tarda is a facultative intracellular pathogen in humans and animals. There is no effective way except vaccine candidates to eradicate intracellular E. tarda. In this study, four derivatives of marine peptide-N6NH2 were designed by an introduction of unnatural residues or substitution of natural ones, and their intracellular activities against E. tarda were evaluated in macrophages and in mice, respectively. The minimum inhibitory concentration (MIC) value of N6NH2 and GUON6NH2 against E. tarda was 8 μg/mL. GUON6NH2 showed higher stability to trypsin, lower toxicity (<1%) and longer post-antibiotic effect (PAE) than N6NH2 and other derivatives. Antibacterial mechanism results showed that GUON6NH2 could bind to LPS and destroyed outer/inner cell membranes of E. tarda, superior to N6NH2 and norfloxacin. Both N6NH2 and GUON6NH2 were internalized into macrophages mainly via lipid rafts, micropinocytosis, and microtubule polymerization, respectively, and distributed in the cytoplasm. The intracellular inhibition rate of GUON6NH2 against E. tarda was 97.05–100%, higher than that in case of N6NH2 (96.82–100%). In the E. tarda-induced peritonitis mouse model, after treatment with of 1 μmol/kg N6NH2 and GUON6NH2, intracellular bacterial numbers were reduced by 1.54- and 1.97-Log10 CFU, respectively, higher than norfloxacin (0.35-Log10 CFU). These results suggest that GUON6NH2 may be excellent candidates for novel antimicrobial agents to treat infectious diseases caused by intracellular E. tarda.